Analisis Pertumbuhan Keausan Pahat Pada Pembubutan Material Mild Steel - Lubis, Muhammad Sobron Yamin; Riza, Abrar; Michel, John; Ariyanti, Silvi (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
The study of wear on tool blades when cutting metal is important because it influences work results and production costs. Increasing metal hardness demands durability and strength of the chisel bit. Long periods of use and high speeds can cause wear, damage the chisel, and affect the quality of the results and production costs. This research uses a CNC lathe with a carbide cutting edge to cut mild steel. The cutting speed varies between 170 to 190 m/min with a cutting pass of 0.3 mm/revolution, a cutting depth of 0.7 mm, and a wear criterion of 0.3 mm. Turning was carried out for 2.5 minutes, then wear was observed using an optical electron microscope. The results show abrasive wear on the side of the chisel blade (flank wear) due to friction. A cutting speed of 190 m/min took 7:25 minutes, 180 m/min took 8:09 minutes, and 170 m/min took 8:36 minutes. This research proves that cutting speed influences wear rates, with wear primarily caused by abrasive friction.